The impact of unit delimitation on exegesis - Hoop, Raymond de; Korpel, Marjo C. A. (Marjo Christina Annette), 1958-; Porter, Stanley E., 1956- (Pericope ;, 2009)
Contains papers dealing with the impact of unit delimitation on exegesis. This volume includes contributions on the Books of "Genesis", "Isaiah", "Jeremiah", "Daniel", "Hosea", "Nahum", "Habakkuk", "Romans", and "Mark". It also discusses the delimitation of units in "Genesis", "Isaiah 56:1-9", and "Jeremiah and Habakkuk."